Fluorescent delivery vehicle containing cobalt oxide–umbelliferone nanoconjugate: DNA/protein interaction studies and anticancer activity on MF7 cancer cell line. Issue 45 (23rd August 2019) - Ali, Mohd Sajid; Tabassum, Sartaj; Al-Lohedan, Hamad A.; Farah, Mohammad Abul; Al-Anazi, Khalid Mashay; Usman, Mohammad
Abstract : Model of drug-nanoconjugate with DNA and HSA. Abstract : Fluorescent labeling is limited to certain molecules and alters biomolecule functionality. A new class of nanomaterial with anticancer activity and fluorescence properties has been designed and prepared. This nanotherapeutic conjugate of natural molecules has a selective binding site in cancer cell lines. Natural drug umbelliferone was taken with cobalt metal ions in a one pot assembly in the presence of tannic acid which yields new fluorescent nanoparticles of umbelliferone cobalt oxide nanoconjugate. Umbelliferone has high fluorescent properties and also has coordination ability to bind with central metal ions. The nanoconjugate was synthesized and characterized by using TEM, EDX analysis, SEM, XRD, and FTIR spectroscopy. TEM shows that the average size of the particles formed with umbelliferone is ∼20 nm. The solubility of the drug nanoparticles in water showed compatibility with cancer cells and provided a favorable environment to investigate the mechanism of action on the MCF-7 cell line. The nanoconjugate is microcrystalline in nature and gives a clear suspension in water. The nanocobalt conjugate was loaded on TiO2 nanoparticles by ultrasonication, and the solution was digested overnight. The conjugate of the drug with a TiO2 drug carrier was stable in solution and maintained the nanostructure ∼34.6 nm. A comparative study with nano-vehicle TiO2 and the nanoconjugate was performed. TiO2 was used to compare the anti-cancer activity of the nanoconjugate at low dose in vitro . It was observed that the nanoconjugate with TiO2 is capable of reaching the specific target like the TiO2 nanoparticle and enhance the chemotherapeutic impact. Hence, the nanoconjugate can also be used like nano-TiO2, as the drug and carrier. The ct-DNA and HSA protein binding studies were done and validated by docking studies.